Penentuan Siswa Berprestasi Dengan Metode Simple Additive Weighting Berbasis Web - Randi Rian Putra; Cendra Wadisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Decision support system (SPK) is one part of the information system that uses problem solving in decision making. The selection of high achieving students in Yapim High School and Vocational School Taruna Marelan discusses based on the highest grades, the activeness and concern of students towards the teacher and also based on the rankings of the guardians of each class that are counted manually with the Microsoft excel application, therefore the application required problem solving application Web-based outstanding students. Data obtained through teachers and homeroom teachers who teach at Yapim Taruna Marelan High School and Vocational School, the method used in this application is weighting simple additives (SAW) in the assessment of student achievement based on data from student and high school students 'and Yapim Taruna's students' judgment Marelan This application is used to facilitate teachers and homeroom teachers in favor of outstanding students and also transparent by all students. This system is applied to support decisions made by humans from manual to digital and can be shown in full which becomes an assessment made by the user and proven by the system.